The effect of structural risks on financial downturns - Martin Hodula; Jan Janků; Lukáš Pfeifer (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2022)
We investigate the extent to which various structural risks exacerbate the materialization of cyclical risk. We use a large database covering all sorts of cyclical and structural features of the financial sector and the real economy for a panel of 30 countries over the period 2006Q1-2019Q4. We show that elevated levels of structural risks may have an important role in explaining the severity of cyclical and credit risk materialization during financial cycle contractions. Among these risks, private and public sector indebtedness, banking sector resilience and concentration of real estate exposures stand out. Moreover, we show that the elevated levels of some of the structural risks identified may be related to long-standing accommodative economic policy. Our evidence implies a stronger role for macroprudential policy, especially in countries with higher levels of structural risks.
Keywords: E32; G15; G21; G28; 330; Cyclical risk; event study; financial cycle; panel regression; structuralrisks; systemic risk